1978. Efficacy of Eravacycline in Secondary Bacteremia: A Post Hoc Analysis of Two Phase 3 studies of Complicated Intra-Abdominal Infection. (26th November 2018) - Lawrence, Kenneth; Olesky, Melanie; Izmailyan, Sergey; Tsai, Larry
Abstract: Background: Eravacycline is a novel, fully synthetic fluorocycline antibiotic that was evaluated for the treatment of complicated intra-abdominal infections (cIAI) in two Phase 3 (IGNITE1 and IGNITE4) clinical trials. The objective of this analysis was to evaluate microbiological response at the test of cure (TOC) visit in patients with baseline bacteremia who received eravacycline vs. comparators (ertapenem and meropenem). Methods: Pooled data from IGNITE1 and IGNITE4 studies were analyzed. All patients enrolled were randomized (1:1) to receive eravacycline (1 mg/kg IV q12h) or ertapenem 1 g IV q24h, (IGNITE1 study) or meropenem 1g IV q8h, (IGNITE4 study) for 4–14 days. Blood (aerobic and anaerobic bottles) and intra-abdominal samples were collected from all patients. Clinical outcome at the TOC visit (28 days after randomization) in the microbiological-intention to treat population (micro-ITT) was the primary efficacy endpoint. Results: Four hundred fifteen patients were treated with eravacycline and 431 with comparators of which 39 (9.4%) and 40 (9.3%), respectively, had concurrent bacteremia. Demographic and baseline characteristics were similar among the groups. In the micro-ITT population, the pooled clinical response at the TOC visit for eravacycline vs. comparators was 88.7% and 89.3% (−0.7; 95% CI, −4.9, 3.6), respectively. The baseline pathogens associated with concurrent bacteremia and the microbiological eradication for selected pathogens are presented in Table 1. Conclusion: Eravacycline demonstrated a similar microbiological eradication rate as comparator agents in patients with cIAI associated with secondary bacteremia. Disclosures: K. Lawrence, Tetraphase Pharmaceuticals: Employee, Salary. M. Olesky, Tetraphase Pharmaceuticals: Employee and Shareholder, Salary. S. Izmailyan, Tetraphase Pharmaceuticals: Employee, Salary. L. Tsai, Tetraphase Pharmaceuticals: Employee and Shareholder, Salary.